The Democracy Index: On the scientific practice of norming democracy as an instrument of political power - Stefan, Barbara (Momentum Quarterly, 2015)
Democracy Indices are a central component of Global Governance – a discourse as well as a political-strategic regulation process, which, in the name of coping cooperatively with worldwide challenges (currently more sustainability in dealing with climate change), also advances a neoliberal, financialized remodeling of state and society. Exemplified by the “Combined Index of Democracy” the present article shows how this method of comparative political science contributes in stabilizing a historically specific, sociopolitical relation of social inequality as desirable normality. The index is based on a certain “imaginary” of democracy and produces its “inscription”, which blinds out the historic legitimatory process of the legal stipulation of economic inequality through guaranteeing political equality and competitive possibilities of participation. The purpose of the formalized, objective and (in the case of the CID) comprehensive measurement of the quality of democracy is the production of a fixed, true object of knowledge that immutably and mobile carries on its meaning into different contexts. Such a normed democracy neutralizes bourgeois property interests and grants political rationality and legitimacy to a post-fordistic governmentality.